Optimization of the Role of Naval Intelligence to Support Lanal Denpasar in Enhancing Security in the Bali Waters - Hidayat, Samsul Rachmad; Zulkifli, Muhammad; Achsyan, Dewadharu (Journal of Industrial Engineering & Management Research, 2025)
— Indonesia's geographical location, situated at the crossroads of two oceans and two continents, makes it vital in global maritime trade and communication routes. The waters of Bali have a high shipping traffic density and face potential maritime threats such as smuggling, illegal fishing, and transnational crimes. The Indonesian Navy, through Lanal Denpasar, plays a crucial role in maintaining security and conducting early threat detection in these waters. However, Lanal Denpasar faces challenges related to the limited quantity and quality of intelligence personnel, as well as inadequate intelligence facilities and infrastructure, which hinder the effectiveness of the Navy's intelligence role. This study aims to analyze the role of naval intelligence in supporting Lanal Denpasar to enhance security in the Bali waters. The research method used in this study is qualitative. The findings suggest that increasing the number and quality of trained intelligence personnel in the Bali waters, along with fulfilling the necessary intelligence infrastructure, is crucial for detecting threats such as smuggling and illegal fishing. Through inter-agency cooperation and the utilization of advanced technology, this policy aims to strengthen early detection, quick response, and maintain maritime stability and national sovereignty. This effort is expected to enhance security and support more effective security policies in the Bali waters.